Electrochemical Determination of Nicotine in Tobacco Products Based on Biosynthesized Gold Nanoparticles - Jing, Yanqiu; Ning, Shanghui; Guan, Yu; Cao, Mingfeng; Li, Junju; Zhu, Li; Zhang, Qili; Cheng, Chuance; Deng, Yong (Frontiers in Chemistry, 2020)
In this work, gold nanoparticles were biosynthesized using Plectranthus amboinicus leaf extract as the reducing agent. A series of techniques were used for sample analysis. The biosynthesized gold nanoparticles (bAuNPs) are a uniform size with a spherical shape. The FTIR analysis reveals the presence of many oxygen-containing functional groups on the bAuNP surface. The cyclic voltammetry and electrochemical impedance spectroscopic characterizations reveal that while the bAuNPs have a slightly lower conductivity than chemically synthesized AuNPs (cAuNPs), the bAuNPs have a superior electrocatalytic performance towards nicotine reduction. After optimization, the bAuNP-modified SPE could detect nicotine linearly from 10 to 2000 μM with a low detection limit of 2.33 μM. In addition, the bAuNPs/SPE have been successfully used for nicotine-containing-product analysis.